(RE)-INTERPRETATION OF THE PAER SPACE CONCEPT AN ENVIRONMENTAL PATTERN APPROACH THROUGH A MULTILEVEL - Taufan Hidjaz Ovan (Department of Architecture, Faculty of Science and Technology, UIN Maliki Malang, 2021)
Lombok is called the Island of Thousand Mosques. Its inhabitants from the Sasak ethnic group are Muslim, who have the concept of the Paer space. It is a place of the existential transience of life, and the center is a mosque. The Paer space is implemented to have a hierarchy from a family cluster environment called paer bale langgak, paer dusun, paer village, and paer cardinal area, which function as the places for worship and culture to spend their remaining time towards an eternal time in the afterlife. This study identifies how religious, social, and cultural activities in the Paer space are centered on the mosque's architecture and interprets the patterns of the community behavior that influence each other in it. The concept of Paer or temporary existential space is then reinterpreted using descriptive-analytical-qualitative methods to obtain a schematic environmental pattern that can be developed adaptively in Muslim communities with mosque as the center of orientation for worship and cultural activities.